Local Wisdom and Social Dilemma Has Allergy Upon Worn Value, Proudly with Currently Values (Viewed from Social Anthropology Perspective for Orang Ocu) - Syafrizal Syafrizal (RIRAI Publisher, 2021)
It is noted that local wisdom is considered as an adjustable thing, flexible so that in variously social element openly to discuss it out. The main topics to discuss is to correlate local wisdom phenomenon and also found a social dilemma might arise there, such as communal activities recorded public see allergic with any old values, having proudly with newly values, it is all viewed from social anthropology perspective. This research has been done in qualitative approach within a very long time duration period calculated in completing Doctoral program in study, still to do re-study ( another research ) only done them in a short time, it has already data previously reasonable, in this case to community of Ocu on Kabupaten Kampar Riau. Accordingly, a partly of the study is categorized as ethnography research due to the source of data originally from informants chosen purposively under consideration of appropriately quality, figurative value, or someone as considered someone with much knowledge about the topic is discussing to. This study has found own very high strategic values which things can be set as instrument for criticizing even in this case with own initiative to commence re-repairmen particularly to its cultural values holed by local people whose neglect own old cultural values available, unfortunately in highly obsession to receive newly cultural values at any time having not comfortable however with the living pattern and their character in daily life, thence emerging in what generally called lost cultural with local condition is well known with “aghokkan ujan dilangik, ayu dikulam babuangkan”.